Skan linii papilarnych jako podpis elektroniczny - Klimas, Damian (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
Presented article addresses the issue of regulation concerning the submission of electronic statements statements of intent, a statement knowledge or consent using a scan of a fingerprint understood as an electronic signature. The author tries to find the appropriate framework for the fingerprint scan as an electronic signature under eIDAS Regulation, which is applicable since 1 July 2016. Article analyses the technical and legal requirements for electronic signatures, advanced electronic signatures and qualified electronic signatures, as well as the legal consequences of such determinants.
Keywords: eIDAS; electronic signature; fingerprint; QES; AES